Pattern of Coronary Artery Disease in Patients with Left Bundle Branch Block in Acute Coronary Syndrome - Liaqat, Hafsa; Adil, Mohammad; Khan, Faraz Ali; Ali, Mohammad (Indus Journal of Bioscience Research, 2025)
Background: Left bundle branch block is a common manifestation at presentation of patients with acute coronary syndrome and is most often associated with coronary artery disease. However, CAD pattern of the patient, specifically with consideration of demographic factors like age, gender, as well as socioeconomic status, must be investigated. Knowledge of burden as well as prevalence of CAD in ACS patients with LBBB will help manage as well as diagnose effectively. Objective: To determine the frequency of pattern of coronary artery disease in patients with left bundle branch block in acute coronary syndrome. Study Design: Cross-sectional study. Study Duration and Setting: The study was conducted from August 2024 to February 2025 at the Department of Cardiology, LRH Peshawar. Methodology: The study consisted of 111 patients aged 30-70 with ACS and LBBB. Demographic data, including sex, age, BMI, and socioeconomic status, were elicited. Coronary angiography was done for the patients to find the number of blockages of coronary artery and its location. CAD was graded as single-vessel disease, double-vessel disease, or triple-vessel disease. Results: The majority of patients were male (79.3%), with a mean age of 58.60 ± 6.94 years. The most common CAD pattern was SVD (48.6%), followed by TVD (29.7%) and DVD (18%). Significant associations were found between socioeconomic status and CAD patterns, with middle-class patients having a higher incidence of SVD. Conclusion: Left bundle branch block (LBBB) is frequently associated with coronary artery disease in patients with acute coronary syndrome, with a predominant pattern of single-vessel disease.